2014
DOI: 10.1108/ijppm-01-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Korean and US continuous improvement projects

Abstract: Purpose – Quality Circles and Kaizen Events have resulted in productivity and quality improvements for organizations. There is limited empirical research comparing these two approaches. This research study was designed to understand the similarities and differences in the structure and outcomes of these two popular continuous improvement approaches in Korea and the USA. The paper aims to discuss these issues. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Kaizen events represent swift and radical implementations of Kaizen at the team level (Van Dun and Wilderom, 2016;Hirzel et al, 2017). Kaizen offers several benefits, including improved productivity, waste reduction, increased profit, client satisfaction, quality enhancement and competitive advantage (Jin and Doolen, 2014).…”
Section: Kaizen Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaizen events represent swift and radical implementations of Kaizen at the team level (Van Dun and Wilderom, 2016;Hirzel et al, 2017). Kaizen offers several benefits, including improved productivity, waste reduction, increased profit, client satisfaction, quality enhancement and competitive advantage (Jin and Doolen, 2014).…”
Section: Kaizen Eventsmentioning
confidence: 99%
“…Kaizen offers several benefits, including improved productivity, waste reduction, increased profit, client satisfaction, quality enhancement and competitive advantage (Jin and Doolen, 2014).…”
Section: Kaizen Eventsmentioning
confidence: 99%
“…Quality Improved quality a) [18] b) [19] c) [20] d) [19] QCs improved quality. QCs improved quality.…”
Section: Source Findingmentioning
confidence: 99%
“…Besides the above approaches of CI, other approaches are practised in organisations to improve quality. Some studies showed that different approaches to CI are equally effective in driving improvements in both technical and social systems, even though there are significant differences in the project size, type, location, and industrial sector (Jin & Doolen, 2014). Another study found out that the success of the use of CI approaches depends on the culture of the organisation and the capability of the managers and leaders to implement those approaches effectively (Robinson & Phuong, 2015).…”
Section: Conventional Approaches To Continuous Quality Improvementmentioning
confidence: 99%